قراءة ثقافية فى سيفية المتنبى "غيرى بأكثر هذا الناس ينخدع" - محمد، هاني علي سعيد Mohammed, Hani Ali Said (جامعة قناة السويس - كلية الآداب والعلوم الإنسانية, 2016)
A cultural reading of one of Mutanabi’s Saifiat (Al- Mutanabbi’s poems to Saif Al-Dawla): entitled "Unlike me, many are deceived this" The current research does contrastively explore how eulogy can be converted into defamation in one of (Al-Mutanabbi’s Saifiat where he eulogized Saif Al-Dawla and described on of his lost battles. The present study deployed a cultural reading approach that investigates the text within its cultural patterns and various backgrounds in an attempt to disclose the unsaid and the implicit in discourse. It became clear in the present study sections how Al-Mutanabbi did not abide by the historical authority while writing his introduction to the investigated Saifia. This is underscored in our investigation of the deceptive patterns and the falsification of discourse; moreover, the researcher observed how contrastive pairs novel patterns such as eulogy that generates defamation, authoritarianism that breeds self-verification. Furthermore, the researcher perfected a cultural reading for intertextuality and hyperbole due to their remarkable roles as sources of discourse aesthetics in Saifiat.
قلب سيفيات المتنبي من المديح إلى الهجاء؛ قراءة ثقافية في سيفية: غيري بأكثر هذا الناس ينخدع". يدرس هذا البحث على نحو مغاير كيف ينقلب المديح إلى هجاء في واحدة من سيفيات المتنبي، التي يمدح فيها سيف الدولة ويصف إحدى معاركه التي هُزم فيها سنة 339ه، ولقد جاء ذلك عبر تفعيل القراءة الثقافية، التي تقوم برد النص للأنساق الثقافية التي أنتته، وفتحه علي المرجعيات المختلفة في محاولة لإظهار المضمر والمسكوت عنه في الخطاب. وفي مباحث الدراسة بدا إلغاء المتنبي لسلطة التاريخ على نصه من خلال ما كتبه لسيفيته من مقدمة، وهو ما حللناه في دراستنا للنسق المخاتل وتزييف الخطاب، كما رصدنا قدرة الثنائيات الضدية على توليد أنساق جديدة؛ كالمديح المولد للهجاء، وتضخم السلطة المولد لإثبات الأنا، بالإضافة إلى ما قدمناه من قراءة ثقافية للتناص والمبالغة بوصفهما من جماليات الخطاب في السيفية.
Keywords: الشعر العربى -- النقد الأدبى -- سيفيات المتنبى -- الأدب العربى - تاريخ ونقد -- الشعر العربى - تاريخ ونقد